<span>Simplifying
4(y + -3) = 6(y + 2)
Reorder the terms:
4(-3 + y) = 6(y + 2)
(-3 * 4 + y * 4) = 6(y + 2)
(-12 + 4y) = 6(y + 2)
Reorder the terms:
-12 + 4y = 6(2 + y)
-12 + 4y = (2 * 6 + y * 6)
-12 + 4y = (12 + 6y)
Solving
-12 + 4y = 12 + 6y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-6y' to each side of the equation.
-12 + 4y + -6y = 12 + 6y + -6y
Combine like terms: 4y + -6y = -2y
-12 + -2y = 12 + 6y + -6y
Combine like terms: 6y + -6y = 0
-12 + -2y = 12 + 0
-12 + -2y = 12
Add '12' to each side of the equation.
-12 + 12 + -2y = 12 + 12
Combine like terms: -12 + 12 = 0
0 + -2y = 12 + 12
-2y = 12 + 12
Combine like terms: 12 + 12 = 24
-2y = 24
Divide each side by '-2'.
y = -12
Simplifying
y = -12</span>
Answer:
Answer is in picture
Step-by-step explanation:
Hope it is helpful.......
X2 minus x1/y2 minus y1 is how u find slope
Answer:
7/7
Step-by-step explanation:
Add up the amount of the marbles in total and read what color the marble they ask for the chances of. The color of marble should go first then the total of the marbles. (they could ask for more than one color so just add up both the colors given.)
Thank you for posting your question here at brainly. I hope the answer will help you. Feel free to ask more questions.
<span>(t) = 0 gives
</span><span>-24t + 60 = 0
</span><span>t = 2.5
</span><span>For this t, the second derivative s"(t) = -24 is negative. And so, s(t) is maximum for t = 2.5.
</span><span>Maximum height is S = -12(2.5)^2 + 60(2.5) +8 = 233ft</span>